2000
DOI: 10.1161/01.cir.102.21.2643
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Direct Role for Calcium in Ischemic Diastolic Dysfunction in Isolated Hearts

Abstract: Background-Ischemia is characterized by an increase in intracellular calcium and occurrence of diastolic dysfunction. We investigated whether the myocyte calcium level is an important direct determinant of ischemic diastolic dysfunction. Methods and Results-We exposed isolated, perfused isovolumic (balloon in left ventricle) rat and rabbit hearts to low-flow ischemia and increased extracellular calcium (from 1.5 to 16 mmol/L) for brief periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
2
13
0
1
Order By: Relevance
“…The results support a mechanism of ATP depletion directly affecting cross-bridge detachment underlying increased diastolic chamber stiffness during ischemia. However, previous studies, including ours (10,23,37), have failed to demonstrate a lower average tissue [ATP] in hearts subjected to either supply or demand ischemia, in which an increase in diastolic chamber stiffness occurred, compared with hearts subjected to similar ischemia, in which no increase in diastolic tension occurred. Thus the degree of diastolic dysfunction sustained failed to correlate with the level of depletion of high-energy phosphates during ischemia (32).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The results support a mechanism of ATP depletion directly affecting cross-bridge detachment underlying increased diastolic chamber stiffness during ischemia. However, previous studies, including ours (10,23,37), have failed to demonstrate a lower average tissue [ATP] in hearts subjected to either supply or demand ischemia, in which an increase in diastolic chamber stiffness occurred, compared with hearts subjected to similar ischemia, in which no increase in diastolic tension occurred. Thus the degree of diastolic dysfunction sustained failed to correlate with the level of depletion of high-energy phosphates during ischemia (32).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, attempts to correlate observations of increasing myocyte calcium concentration to development of contracture do not necessarily confirm cause-effect relationships. Thus some studies (2,20) reported no correlation, and increased diastolic calcium, assessed by calcium indicators, may not reflect troponin C-bound calcium (10). In contrast to these previous studies, here we assessed responses to interventions designed to differentiate calcium-versus rigor-mediated mechanisms, after stiffness had increased.…”
Section: Discussionmentioning
confidence: 98%
“…In conclusion, the findings presented in this study demonstrated that Ca 2ϩ handling abnormalities occur in cardiomyocytes isolated from I/R hearts and that this alteration is dependent on the period of ischemic insult. ] i in intact heart (10,20,24,25). This view is based on the observations that diastolic Ca 2ϩ measurements in the intact heart are associated with methodological problems including motion artifacts of beating hearts, absorbance of light by chromatic molecules, contribution of changes in signal due to the presence of other types of cells, and the effect of temperature/pH on the intracellular Ca 2ϩ -induced signal emission (38).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a positive correlation was found to occur between the diastolic intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) and left ventricular end-diastolic pressure (LVEDP) in I/R rat hearts (25); however, such a relationship was not evident in postischemic ferret myocardium (20,24). In fact, some investigators (10) have denied a direct role of intracellular Ca 2ϩ in ischemic diastolic dysfunction in isolated rat and rabbit hearts. Although different studies have examined the Ca 2ϩ handling ability of cardiomyocytes obtained from I/R hearts or undergoing hypoxia-reoxygenation, the results are conflicting (4,21,32,34).…”
mentioning
confidence: 99%
“…A number of recent experimental studies argue in favor of the second hypothesis. Eberli et al (3) were able to show that when Ca 2ϩ availability was experimentally altered during ischemia, there was no alteration in LV diastolic pressure, suggesting that ischemic diastolic dysfunction is not directly mediated by extra Ca 2ϩ -activated tension. Similarly, using NMR spectroscopy for direct measurement of high-energy phosphate and [Ca 2ϩ ] during a prolonged period of ischemia, Koretsune and Marban (10) demonstrated that a fall in ATP coincides closely with the onset of contracture, whereas the profound intracellular acidosis and P i accumulation during ischemia render the myofilaments insensitive to Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%